Current progress in immunotherapy for pancreatic cancer. Issue 1 (10th October 2016) - Foley, Kelly; Kim, Victoria; Jaffee, Elizabeth; Zheng, Lei
Highlights: Pancreatic cancer remains one of the most lethal cancers with few treatment options. Immune-based strategies are showing promise where other approaches have failed. Immunotherapies include immune checkpoint inhibitors and therapeutic vaccines. Combining immune checkpoint inhibitors with therapeutic vaccines is most effective. Abstract: Pancreatic cancer remains one of the most lethal cancers with few treatment options. Immune-based strategies to treat pancreatic cancer, such as immune checkpoint inhibitors, therapeutic vaccines, and combination immunotherapies, are showing promise where other approaches have failed. Immune checkpoint inhibitors, including anti-CTLA4, anti-PD-1, and anti-PD-L1 antibodies, are effective as single agents in immune sensitive cancers like melanoma, but lack efficacy in immune insensitive cancers including pancreatic cancer. However, these inhibitors are showing clinical activity, even in traditionally non-immunogenic cancers, when combined with other interventions, including chemotherapy, radiation therapy, and therapeutic vaccines. Therapeutic vaccines given together with immune modulating agents are of particular interest because vaccines are the most efficient way to induce effective anti-tumor T cell responses, which is required for immunotherapies to be effective. In pancreatic cancer, early studies suggest that vaccines can induce T cells that have the potential to recognize and kill pancreatic cancer cells, but the tumor microenvironment inhibits effective T cell trafficking and function. While progress has been made in the development of immunotherapies for pancreatic cancer over the last several years, additional trials are needed to better understand the signals within the tumor microenvironment that are formidable barriers to T cell infiltration and function. Additionally, as more pancreatic specific antigens are identified, immunotherapies will continue to be refined to provide the most significant clinical benefit.